PENGARUH NON PERFORMING LOAN (NPL) TERHADAP KINERJA KEUANGAN PT. BANK MANDIRI (PERSERO) TBK KANTOR CABANG SUNGGUMINASA - Dirwan Dirwan (AkMen JURNAL ILMIAH, 2016)
The aim of the study was to: 1) Know and analyze effect of Non Performing Loan (NPL) to Financial Performance Bank Mandiri. 2) Know and analyze how much influence of Non Performing Loan (NPL) to Financial Performance Bank Mandiri. The study was conduted at the PT. Bank Mandiri (Persero) Tbk Sungguminasa Branch. The source of the data in this research is secondary data, particularly with respect to the quarterly financial statements PT. Bank Mandiri (Persero) Tbk, from 2013 until 2015.. The data analyzed used was simple regression analysis. The result of study indicate that 1) Non Performing Loan (NPL) has negative and significant influence to Financial Performance Bank Mandiri with indicators’ Return on Assets (ROA). 2) Amounting to 0.889 or 88.9% Non Performing Loan (NPL) may affect the Bank's financial performance with indicators’ Return on Assets (ROA).